2020
DOI: 10.1007/s00421-020-04388-4
|View full text |Cite
|
Sign up to set email alerts
|

Exceeding a “critical” muscle Pi: implications for $$\dot{\text{V}}\text{O}_{2}$$ and metabolite slow components, muscle fatigue and the power–duration relationship

Abstract: This is a repository copy of Exceeding a "critical" muscle Pi: implications for V˙O2 and metabolite slow components, muscle fatigue and the power-duration relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(65 citation statements)
references
References 49 publications
8
56
1
Order By: Relevance
“…While the power-duration relationship in the severe exercise intensity domain has been well investigated based on the CP concept (Jones et al 2010 ; Poole et al 2016 ), limited research exists on deriving the power-duration relationship in the moderate and heavy exercise intensity domains (Black et al 2017 ). Hence Puchowicz et al ( 2020 ) and Peronnet and Thibault ( 1989 ) proposed mathematical models with an aerobic decay term, but limited research exists to assess if these concepts have a high predictive ability for the power-duration relationship in the moderate and heavy exercise intensity domains in relation to the muscle bioenergetic system (Korzeniewski 2019 ; Korzeniewski and Rossiter 2020 , 2021 ; Vanhatalo et al 2016 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…While the power-duration relationship in the severe exercise intensity domain has been well investigated based on the CP concept (Jones et al 2010 ; Poole et al 2016 ), limited research exists on deriving the power-duration relationship in the moderate and heavy exercise intensity domains (Black et al 2017 ). Hence Puchowicz et al ( 2020 ) and Peronnet and Thibault ( 1989 ) proposed mathematical models with an aerobic decay term, but limited research exists to assess if these concepts have a high predictive ability for the power-duration relationship in the moderate and heavy exercise intensity domains in relation to the muscle bioenergetic system (Korzeniewski 2019 ; Korzeniewski and Rossiter 2020 , 2021 ; Vanhatalo et al 2016 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…Regardless of the relative importance of either of these mechanisms, the key attribute to both is an increase in the [P i ] and [H + ] in the working muscles. Indeed, it has been shown that the slow component is preceded by muscular fatigue, 68 and recent modeling studies have implicated elevated [P i ] per se on the apparent reduction in muscle efficiency and development of the slow component, whereby the slow component occurs only after a critical threshold of [P i ] in the muscle is reached 69 . While this notion would explain the assumed delay in the onset of the slow component, it should be pointed out that the apparent time delay of the slow component has also been suggested to be an artifact of common mathematical modeling procedures to V̇O 2 data, without a true physiological basis 70 .…”
Section: The Effect Of Fatigue On Cycling Efficiencymentioning
confidence: 99%
“…The concentration of Mg 2+ , which was released from MgATP also increased with the consumption of ATP [ 106 ]. However, normal exercise does not substantially reduce the ATP concentration in muscles [ 25 , 107 , 108 ], but rather a large amount of ADP is generated as a by-product [ 108 ]. ADP does not maintain RyR activity as efficiently as ATP [ 24 ].…”
Section: Ryr Regulation Under Different Muscle Conditionsmentioning
confidence: 99%